1989
DOI: 10.1111/j.1600-051x.1989.tb01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal influences on gingival tissue: relationship to periodontal disease

Abstract: It is the purpose of this review to survey the influence of corticosteroids, androgens, oestrogens and progesterone on gingival tissues and to show the relationship of such influences to periodontal disease. The clinical changes seen in plaque-induced gingivitis are accentuated by circulating levels of the above hormones via mechanisms such as partial immune suppression, increased fluid exudation, stimulation of bone resorption and stimulation of fibroblast synthetic activity. High counts of Bacteroides interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
32

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 53 publications
(60 reference statements)
3
95
1
32
Order By: Relevance
“…Increased oral burden of cortisol (via blood, gingival crevicular fluid, and saliva) in the malnourished child may provide selective nutrient advantage to certain specific micro-organisms (Kornman and Loesche, 1980;Loesche et al, 1982;Sooriyamoorthy and Gower, 1989) and promote bacterial invasion of the interdental region through weakening of the host's inflammatory response or by inducing relative ischemia in the gingival papillary region (Johnson and Engel, 1986;Melnick et al, 1988). The latter offers some plausible explanation for the wellknown association between stress, including the stress of malnutrition and/or infections, and the occurrence of ANG (Melnick et al, 1988).…”
Section: Risk Factors For Nomamentioning
confidence: 99%
“…Increased oral burden of cortisol (via blood, gingival crevicular fluid, and saliva) in the malnourished child may provide selective nutrient advantage to certain specific micro-organisms (Kornman and Loesche, 1980;Loesche et al, 1982;Sooriyamoorthy and Gower, 1989) and promote bacterial invasion of the interdental region through weakening of the host's inflammatory response or by inducing relative ischemia in the gingival papillary region (Johnson and Engel, 1986;Melnick et al, 1988). The latter offers some plausible explanation for the wellknown association between stress, including the stress of malnutrition and/or infections, and the occurrence of ANG (Melnick et al, 1988).…”
Section: Risk Factors For Nomamentioning
confidence: 99%
“…Considering the strong correlation between calculus accretion and periodontal disease as discussed above, this lack of consistency in the pattern of sex difference between calculus accretion and alveolar resorption is unexpected. The previous studies using clinical data suggest there are multiple factors contributing to periodontal disease, including smoking, diabetes, and the stresses related to the female life history (menstruation, pregnancy, delivery, lactation, and menopause) (Sooriyamoorthy and Gower, 1989;Genco, 1996). Among these factors, calcium deficiency and hormone (estrogens and progesterone) balance changes triggered by female life history might lead to sex differences in alveolar resorption prevalence (Sooriyamoorthy and Gower, 1989;Shoji et al, 2007), although we cannot examine this possibility.…”
Section: Sex Difference Of Oral Disease Prevalencementioning
confidence: 96%
“…However, sex hormones have long been considered to affect periodontal tissues and periodontal disease progression (72,73). Tarkila et al reported that use of HRT did not correlate with periodontal health status, and led to lower numbers of samples positive for the periodontal pathogens P. gingivalis and T. forsythia.…”
Section: Effects Of Menopause On Periodontal Tissuementioning
confidence: 99%